2020
DOI: 10.3762/bjoc.16.58
|View full text |Cite
|
Sign up to set email alerts
|

Direct borylation of terrylene and quaterrylene

Abstract: The preparation of large rylenes often needs the use of solubilizing groups along the rylene backbone, and all the substituents of the terrylenes and quaterrylenes were introduced before creating the rylene skeleton. In this work, we successfully synthesized 2,5,10,13-tetrakis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)terrylene (TB4) by using an iridium-catalyzed direct borylation of C–H bonds in terrylene in 56% yield. The product is soluble in common organic solvents and could be purified without column ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Coincidently, the iridium─ catalyzed tetraborylation of unsubstituted terrylene and quaterrylene was reported by Yamada, Aratani, and co─ workers. 41 Subsequent to our study, several para ─ and meta ─ selective C─ H borylation reactions using steric and/or coordinating effects have been reported, 14 one of which is the recent study on the meta ─ selective borylation of monosubstituted benzenes by Asako, Ilies, and co─ workers. 42 We expect that the further development of catalytic systems will realize perfect regioselectivity in a variety of aromatic systems.…”
Section: . Conclusionmentioning
confidence: 90%
“…Coincidently, the iridium─ catalyzed tetraborylation of unsubstituted terrylene and quaterrylene was reported by Yamada, Aratani, and co─ workers. 41 Subsequent to our study, several para ─ and meta ─ selective C─ H borylation reactions using steric and/or coordinating effects have been reported, 14 one of which is the recent study on the meta ─ selective borylation of monosubstituted benzenes by Asako, Ilies, and co─ workers. 42 We expect that the further development of catalytic systems will realize perfect regioselectivity in a variety of aromatic systems.…”
Section: . Conclusionmentioning
confidence: 90%
“…Yamada and Aratani et al have reported the borylation of terylene and quaterrylenes (Scheme ). ( n = 0 = perylene, n = 1 = terylene, n = 2 = quaterrylene)…”
Section: Transition-metal-catalyzed Borylation Of C–h Bonds In Comple...mentioning
confidence: 99%
“…Yamada and Aratani et al have reported the borylation of terylene and quaterrylenes (Scheme 97). 170 (n = 0 = perylene, n = 1 = terylene, n = 2 = quaterrylene) Mastalerz et al reported a route to a variety of soluble perylenes that hinges on the regioselective diborylation of a dihydroanthracene. Subsequent Suzuki−Miyaura cross-coupling and cyclization led to the desired perylenes (Scheme 98).…”
Section: Transition-metal-catalyzed Borylation Of Aryl C−h Bonds For ...mentioning
confidence: 99%
“…Various synthetic routes were developed by Müllen and colleagues to solve the solubility and characterization issues of terrylene derivatives through introducing tertiary ‐butyl groups at the ortho ‐positions, [16–19] alkyl chains ( n ‐ethyl, n ‐hexyl) at bay ‐positions [17,20] and oxidative cyclodehydrogenation of perylene and naphthalene to yield relatively pure unsubstituted terrylene [21] (Figure 1). There were other reports on partial peri ‐methyl substituted terrylene, [22] fluoro‐terrylene, [23] benzo‐fused terrylenes, [24] ortho ‐borylation of terrylene, [25] bay ‐aryloxy substituted terrylene and azaterrylenes [26] . Comparatively, chemistry of terrylene imides was well explored due to their applications in photovoltaics, dyes, n‐type materials and organic electronics [27–34] .…”
Section: Introductionmentioning
confidence: 99%